4(1x-6)+6=6x-8

Simple and best practice solution for 4(1x-6)+6=6x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(1x-6)+6=6x-8 equation:


Simplifying
4(1x + -6) + 6 = 6x + -8

Reorder the terms:
4(-6 + 1x) + 6 = 6x + -8
(-6 * 4 + 1x * 4) + 6 = 6x + -8
(-24 + 4x) + 6 = 6x + -8

Reorder the terms:
-24 + 6 + 4x = 6x + -8

Combine like terms: -24 + 6 = -18
-18 + 4x = 6x + -8

Reorder the terms:
-18 + 4x = -8 + 6x

Solving
-18 + 4x = -8 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-18 + 4x + -6x = -8 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-18 + -2x = -8 + 6x + -6x

Combine like terms: 6x + -6x = 0
-18 + -2x = -8 + 0
-18 + -2x = -8

Add '18' to each side of the equation.
-18 + 18 + -2x = -8 + 18

Combine like terms: -18 + 18 = 0
0 + -2x = -8 + 18
-2x = -8 + 18

Combine like terms: -8 + 18 = 10
-2x = 10

Divide each side by '-2'.
x = -5

Simplifying
x = -5

See similar equations:

| 6x-1=9x-10 | | 7x+4=3x-52 | | 1r-10=10r+8 | | 4+6(k-8)=8k-38 | | 8-(-16)= | | x^3+5x^2+x^2-5x-12x-60=0 | | 5x(6-3)= | | 4w+5w=51 | | 10(8m+9)=10(6m-3) | | 8x+-8y=5 | | X-366=415 | | -5x+9=2x-4 | | x+3x+54+2x=180 | | 8p-8=8(-6p-8) | | 2x-6x+4=-12 | | 6x^2-8x-11=0 | | 4m^2-36m= | | x(3x+54)(2x)=180 | | 31=9t-13t+7 | | 19-13p=17p-8 | | (-3n+5)(-5.7)= | | 1.5+.3(h-6)=.8h+2 | | -[6x-(3x+5)]=-4-[4(2x-4)-3x] | | 37+3n=-2 | | (5y-4)(6y-7)= | | 5+2k=3k-3 | | (-8x^4+6x+3)+(2x^4-2x^2+7)= | | 10X^4-6X^3+8X^2=0 | | 22j+11=4j-7 | | q=1000+25p+q | | 6+1(8x+12)= | | X-366=314 |

Equations solver categories